Reconceptualising the right of silence as an effective fair trial standard - Jackson, John (Cambridge University Press, 2009)
As the European Court of Human Rights has come to qualify the privilege against self-incrimination and the right of silence in recent decisions, this article argues that the Court has failed to provide a convincing rationale for these rights. It is claimed that within the criminal process the right of silence should be distinguished from the privilege against self-incrimination and given enhanced effect in order to uphold the protective and participatory rights of the defence which come into play when a suspect is called upon to answer criminal allegations.